EXPLOITING SCENARIO PLANNING FOR STRATEGIC ASSESSMENT OF THE EXTERNAL BUSINESS ENVIRONMENT Future insights of the European pet food sector - Lehtinen, Sara (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
The purpose of this study is to explore how scenarios can be exploited in strategic assessment of the external business environment. One of the key challenges for managers worldwide is to adapt their businesses to the ever-changing business environment. As the companies’ external business environment is constantly presenting new opportunities and threats, it is extremely important that companies continuously monitor the possible changes happening around it. As the speed of change rises, assessing the future has become more and more vital. The study was conducted as an exploratory research and the research strategy was influenced by scenario planning and case study strategy. The study examined the European pet food sector from the future point of view. Qualitative study was chosen as research approach and empirical data was collected primarily by seven expert interviews. The secondary data about the sector was applied as complementary empirical data. In the theoretical part of the research it was discovered that nowadays, traditional analysis frameworks are ill-suited for strategic assessment of the external business environment. This is why a self-created combination framework for analysis was employed both as study’s theoretical framework and analysis technique. Furthermore, the framework formed the base for interview questions. Both in theoretical and the empirical part of the study it was found that today, in strategic assessment of the external business environment, besides setting focus on the current situation, it is important to concentrate also on the future. The traditional analysis frameworks offer a good starting point for collecting relevant data but they do not encourage conducting a deeper analysis. By adding characteristics from scenario planning to these more traditional tools, a new analysis framework was created, which ensured the more comprehensive analysis. By understanding the interconnections between discovered phenomena and changes, and by recognizing uncertainties, the user is helped to reflect the environment more profoundly. The contributions of the study are both theoretical and managerial. A new analysis framework strives to answer to the current needs for strategic assessment of external business environment and the framework was tested in the context of European pet food sector. When it comes to managerial contributions, the importance lies in understanding the future. Managers must take future into account and understand that future includes various possibilities which all must be reflected

Tämän tutkielman tarkoituksena oli tarkastella miten skenaarioita voidaan hyödyntää ulkoisen liiketoimintaympäristön strategisessa arvioinnissa. Nykypäivänä ulkoinen liiketoimintaympäristö asettaa enenevässä määrin haasteita yrityksen johdolle, minkä takia ympäristön tarkkailu ja arviointi on erittäin tärkeää. Kun muutoksia tapahtuu yhä nopeammassa tahdissa, tulevaisuuden arviointi muodostuu koko ajan tärkeämmäksi. Tutkimus toteutettiin ekploratiivisena tutkimuksena ja tutkimusstrategia otti vaikutteita sekä tapaustutkimuksesta että skenaariotutkimuksesta. Tutkimuksessa tarkasteltiin Euroopan lemmikkieläinruokasektoria tulevaisuuden näkökulmasta. Tutkimusmenetelmäksi valittiin laadullinen tutkimus ja empiirinen aineisto kerättiin pääasiassa haastattelemalla seitsemää asiantuntijaa sektorin eri aloilta. Täydentävänä aineistona hyödynnettiin alaa koskevaa sekundääridataa. Tutkimuksen teoriaosuudessa havaittiin, että nykyiset analyysimallit eivät nykypäivänä sovellu sellaisenaan käytettäväksi ulkoisessa liiketoimintaympäristön arvioinnissa. Tämän takia tutkimuksen teoreettisena viitekehyksenä, teemahaastattelujen runkona sekä analyysimetodina päädyttiin käyttämään itse luotua mallia, joka pyrki kehittämään perinteisiä analyysimalleja skenaariosuunnittelun piirteitä hyödyntäen. Sekä tutkimuksen teoreettisessa että empiirisessä osuudessa todettiin, että nykypäivänä ulkoisen liiketoimintaympäristön arvioinnissa on tärkeää suunnata tarkastelu nykyhetken lisäksi tulevaisuuteen. Perinteiset mallit ovat hyvä lähtökohta olennaisen tiedon keräämiseen, mutta eivät kannusta käyttäjiään syvempään analyysiin. Lisäämällä skenaariosuunnittelun piirteitä perinteisiin malleihin luotiin uusi analyysimalli, joka ei jätä tiedon analysointia kesken. Mallin avulla tunnistetaan eri ilmiöitä ja muutoksia sekä näiden väliset yhteydet ja epävarmuustekijät. Lisäksi malli ottaa huomioon tulevaisuuden moninaisuuden ja valmistaa käyttäjää varautumaan useaan erilaiseen tulevaisuuteen. Tutkimuksen merkittävin anti on sekä teoreettinen että liikeenjohdollinen. Uusi analyysimalli pyrkii vastaamaan nykypäivän tarpeeseen kun on kyse ulkoisen liiketoimintaympäristön strategisesta arvioinnista. Analyysimallia testattiin Euroopan lemmikkieläinruokasektorin arvioinnissa. Tutkimuksen tärkein liikkeenjohdollinen anti on tulevaisuuden luonteen ja arvioinnin tärkeyden painottaminen. Ei ole vain yhtä tulevaisuutta vaan lukuisia ja nämä kaikki on otettava huomioon